Ethics before Evidence: The Essential Role of IERB Approval in Research Integrity - Khadim, Rehana; Qureshi, Shaista Noor (Pakistan Armed Forces Medical Journal, 2025)
In medical research, where new ideas and discoveries enhance our understanding of life, ethical principles must come before evidence. The Institutional Ethical Review Board (IERB) upholds ethical standards, ensuring that the pursuit of knowledge never compromises human dignity and moral responsibility. Every researcher must first seek the approval of IERB, not as a formality, but as an essential step toward responsible and credible research.1 The idea of ethical review boards is not new. Its roots traced back to the mid-20th century, when the world was confronted with the horrifying violations of human rights during unethical experiments in medicine and science. The Nuremberg Code in 1947 and later the Declaration of Helsinki in 1964 marked the beginning of global awareness about the need to protect research participants.2 Over time, countries and institutions developed their own frameworks to ensure ethical oversight, and the concept of IERB was created as an institutional mechanism to protect participants, promote ethical standards, and uphold research credibility.